The association between speed of transition from initiation to subsequent use of cannabis and later problematic cannabis use, abuse and dependence. (3rd June 2015) - Hines, Lindsey A.; Morley, Katherine I.; Strang, John; Agrawal, Arpana; Nelson, Elliot C.; Statham, Dixie; Martin, Nicholas G.; Lynskey, Michael T.
Abstract Aims To test whether speed of transition from initiation use to subsequent use of cannabis is associated with likelihood of later cannabis dependence and other outcomes, and whether transition speed is attributable to genetic or environmental factors. Design Cross‐sectional interview study. Setting Australia. Participants A total of 2239 twins and siblings who reported using cannabis at least twice [mean age at time of survey = 32.0, 95% confidence interval (CI) = 31.9 – 32.1, range = 22–45]. Measurements Time between initiation and subsequent cannabis use (within 1 week; within 3 months; between 3 and 12 months; more than 1 year later), later use of cannabis and symptoms of DSM‐IV cannabis abuse/dependence. Multinomial regression analyses (comparison group: more than 1 year later) adjusted the association between speed of transition and the outcomes of cannabis daily use, abuse/dependence and treatment‐seeking after controlling for socio‐demographic, childhood, mental health, peer and licit drug factors. Twin modelling estimated the proportion of variance in transition speed attributable to genetic (A), common environment (C) and unique environmental (E) factors. Findings Subsequent use of cannabis within 1 week of initiation was associated with daily use [odds ratio (OR) = 2.64, 95% CI = 1.75–3.99], abuse and/or dependence (OR = 3.25, 95% CI = 2.31–4.56) and treatment‐seeking for cannabis problems (OR = 1.89, 95% CI = 1.03–3.46). Subsequent use within 3 months was associated with abuse and/or dependence (OR = 1.61, 95% CI = 1.18–2.19). The majority of the variation of the speed of transition was accounted for by unique environment factors (0.75). Conclusions Rapid transition from initiation to subsequent use of cannabis is associated with increased likelihood of subsequent daily cannabis use and abuse/dependence.